A DOUBLE-BLIND, PLACEBO-CONTROLLED EVALUATION OF THE ANXIOLYTIC EFFICACY FF AN ETHANOLIC EXTRACT OF WITHANIA SOMNIFERA - Andrade, Chittaranjan (Medknow Publications, 2000)
A double-blind, placebo-controlled study was conducted to evaluate the efficacy an ethanolic extract of Aswagandha (Withania somnifera), in patients with ICD-10 anxiety disorders. The sample comprised 39 subjects, of whom 20 received the drug and 19 received placebo. The two groups were sociodemographically and clinically similar at baseline. At 2 and 6 weeks follow-up, data from approximately 85% of patients in each group were available for analysis. Statistical trends favouring the drug were observed at both time points. At 6 weeks, significantly more patients met a priori response criteria in the drug group (88.2%) as compared with the placebo group (50%). The drug was well-tolerated and did not occasion more adverse effects than did placebo. It is concluded that this ethanolic extract of Withania somnifera has useful anxiolytic potential and merits further investigation.